Reinterpretasi Konsep Fî Sabîl Al-Lâh Sebagai Ashnâf Zakat - Ani Wafiroh (Universitas Islam Negeri Mataram, 2006)
The term jihad fi sabîl al-Lâh is often used to refer to physical war in the path of God. The word, as it is derived from the Qs. al-Tawbah (9): 60, in fact connotes specific and general meanings. The specific meaning of it commonly found in classical ulema’s interpretation is related to the war. This interpretation is based on historical evidence and supported by the literal meaning of Qur’an and the hadith. But such a meaning is now criticized and regarded as going beyond the conceptual boundary of jihad in Islam. This article seeks to explore the general meaning of the term in the works of classical and contemporary Muslim scholars, aimed at offering a more contextual meaning. It shows that the term does not always necessarily mean the physical war in the name of God or religion, but it can be meant as education, human welfare, and social development.